Study internal fixation of subtrochanteric fracture of femur with dynamic hip screw, dynamic condylar screw and proximal femoral nail-a retro-prospective study - Kumar Mishra, Sandeep; C. E., Deepak; Goari, Kushal; Shukla, Shurendra (International Journal of Research in Medical Sciences, 2018)
Background: Sub trochanteric fracture is commonly seen in young adult and middle age man by high velocity trauma. Present study was taken up to study fracture fixation by PFN, DHS and DCS and compare their result in view of union rate, complication, functional out come, operative risk and effectiveness of implant. This study helps to decide appropriate implant for sub trochanteric fracture. In literature comparison of these PFN, DHS, DCS commonly used implants are rare and most of the studies are done in western population by using one or two implants. Methods: Study is done clinically, in a retro to prospective manner by comparing 75 (50 cases retro and 25 cases prospectively) cases of either sex above the age of 18years from May 2010 to May 2014. All fractures are classified by Seinsheimer classification system. Fracture is fixed with DHS, PFN or DCS in 25 cases each. Results: Males with an average age group 21-40-year were commonly affected with right femur fracture due to high velocity RTA. Fracture pattern was commonly type IIC as per seinsheimer classification. Mean union rate and clinical outcome for PFN is high. Conclusions: PFN attempts to combine advantage of a sliding hip screw with those of intramedullary fixation devices. Cases treated with PFN nail have shown easier rehabilitation, less blood loos, less surgical trauma, early mobilization, early rate of fracture union when compared to those cases treated with DHS and DCS barrel plate as per observation of our study. With our study PFN has given us encouraging results over conventional DHS and DCS. Hence, we recommend PFN as better implant for fixation of sub-trochanteric fracture.